KAJIAN PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DESA LABIAN IRA’ANG KECAMATAN BATANG LUPAR KABUPATEN KAPUAS HULU - Tuah, Ignasius; Dirhamsyah, M; Tavita, Gusti Eva (Universitas Tanjungpura, 2019)
Medicinal plants are all types of plants that produce one or more active components that are used for health care and treatment or all parts of plants that are known or believed to have medicinal properties (Allo 2010). The purpose of this study was to determine the types of medicinal plants used by the community, to find out how to mix types of medicinal plants by the people of Labian Ira'ang Village, Batang Lupar Hulu District. This study used the Snowball Sampling technique or carried out in a chain manner by asking for information on the person who had been interviewed or contacted before and so on. Based on the results of research in the field, the people of Labian Ira'ang Village obtained 34 types of medicinal plants which were used for traditional medicine ingredients. The types of medicinal plants used are included in 24 families. The plant parts used by the people of Labian Iraâ€™ang Village as medicine are roots, stems, fruit and leaves, flowers, sap, fruit, skin, rhizomes, tubers, young shoots and shoots. The most widely used part is the leaves of 16 types and the least used Are the seeds, sap, and flower Sofe ach type.Keywords:Â Labian Ira'ang Village, Plant Type, Utilization